Existence and Continuous Dependence for Fractional Partial Hyperbolic Differential Equations - Qixiang Dong; Guangxian Wu; Lanping Zhu (Journal of Function Spaces)
This paper is concerned with a class of fractional hyperbolic partial differential equations with the Caputo derivative. Existence and continuous dependence results of solutions are obtained under the hypothesis of the Lipschitz condition without any restriction on the Lipschitz constant. Examples are discussed to illustrate the results.